Role of bone scintigraphy in the early diagnosis of discitis. Issue 11 (November 1990) - Choong, K; Monaghan, P; McGuigan, L; McLean, R
Abstract : Nine cases of recorded discitis are presented, in which scintigraphy played an important part in the diagnosis. The patients (five men (aged 21-75 years) and four women (aged 40-73 years)) had a history of back pain varying in duration from two days to three months. Final diagnosis was confirmed microbiologically (seven patients) or radiographically (two patients). Bone scintigraphy was a valuable diagnostic procedure for discitis with earlier detection than plain radiography in three patients and similar initial detection to that of third generation computed tomography. Single photon emission computed tomographic imaging increased diagnostic confidence by indicating the involvement of the adjacent vertebral bodies rather than of the pedicles or spinous processes.